2002
DOI: 10.1677/joe.0.1720345
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent potentiation of the beta-cell is a Ca2+-independent phenomenon

Abstract: When isolated rat pancreatic islets are treated with 16·7 mM glucose, a time-dependent potentiation (TDP) of insulin release occurs that can be detected by subsequent treatment with 50 mM KCl ]i was significantly lowered. Protein acylation is implicated in the underlying mechanism of TDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…2A, left panel) (9)(10)(11)(12). Glucose at concentrations higher than 5.5 mm caused TDP in a concentration-dependent manner as previously described (11,12,17), which was significantly augmented by forskolin ( Fig. 2A, left panel).…”
Section: Effects Of Forskolin On Nutrient-induced Time-dependent Potesupporting
confidence: 78%
See 2 more Smart Citations
“…2A, left panel) (9)(10)(11)(12). Glucose at concentrations higher than 5.5 mm caused TDP in a concentration-dependent manner as previously described (11,12,17), which was significantly augmented by forskolin ( Fig. 2A, left panel).…”
Section: Effects Of Forskolin On Nutrient-induced Time-dependent Potesupporting
confidence: 78%
“…We previously reported that cerulenin, which inhibits protein acylation at a concentration of 30 -100 g/ml, specifically inhibits nutrient-induced insulin release and glucoseinduced TDP (12,22). We therefore examined whether protein acylation was involved in the enhancement of nutrient-induced TDP by forskolin.…”
Section: Effects Of Nan 3 and Cerulenin On Forskolin Enhancement Of Tdpmentioning
confidence: 98%
See 1 more Smart Citation
“…By mediating protein-membrane and protein-protein interactions, protein acylation is thought to be important for cell signaling, e.g., in the T cell (25,26,34,39) and ␤-cell (6,31,41,44). We found that inhibitors of protein acylation blocked the distal inhibitory effects of NE, somatostatin, galanin, and PGE 2 .…”
mentioning
confidence: 75%
“…The b-cell priming by glucose occurs in a K ATP channelindependent manner, because the potentiation was totally resistant to a high concentration of diazoxide, an opener of K ATP channels 12 . Furthermore, TDP occurs under stringent Ca 2+ -free conditions and therefore [Ca 2+ ] i elevation is not required 27 . Taken together, these observations suggest that the second phase observed under a square wave high-glucose application is the triggered insulin release followed by enhancement by TDP.…”
Section: Priming Of B-cellsmentioning
confidence: 99%